Green synthesis and characterization of ZnO/α-Fe2O3 nanocomposites using hydrocotyle umbellata leaf extract and evaluation of their antimicrobial properties - Kaliyaperumal, Raja; Nagaraj, Karuppiah; Sakthikumar, Karunganathan; Albeshr, Mohammed F.; Velmurugan, Gunasekaran (Applied organometallic chemistry, 2025)
In this study, ZnO/α-Fe2O3 nanocomposites were synthesized via a green coprecipitation method using Hydrocotyle umbellata leaf extract as a reducing and stabilizing agent. The synthesis involved Zn (NO₃)₂.6H₂O, ferric chloride, and sodium hydroxide in various molar ratios of ZnO/α-Fe₂O₃ (9:1, 8:2, 7:3), followed by calcination at 400°C. The synthesized nanocomposites were analyzed using XRD, FTIR, UV-Vis, and SEM to determine their crystalline structure, functional groups, optical properties, and surface morphology. The XRD analysis confirmed the formation of ZnO and α-Fe₂O₃ phases, whereas FTIR confirmed the presence of metal-oxygen bonds and phenolic compounds from the plant extract. UV-vis analysis showed a redshift in the absorption spectra, indicating a reduction in bandgap energy in ZnO/α-Fe₂O₃ nanocomposites compared to pure ZnO. The SEM results confirmed that the ZnO/α-Fe2O3 composites exhibit excellent crystallinity, with an average crystal size of approximately 39 nm, calculated using the Debye-Scherrer equation. The antimicrobial activity of ZnO/α-Fe₂O₃ nanocomposites was evaluated using the disk diffusion method against Staphylococcus aureus, Escherichia coli, and Aspergillus niger. The ZnO/α-Fe₂O₃ (8:2) formulation showed the strongest antibacterial effect against S. aureus, highlighting its potential for eco-friendly antimicrobial applications.
Zuerst veröffentlicht: 13. März 2025
Gesehen am 13.08.2025
Im Titel sind die Zahlen 2 und 3 tiefgestellt